Analysis of The Best Day To Post A Content on Instagram and Facebook of Hospital A and Hospital B’s Social Media - Nur, Luthfiana (Cakrawala Management Business Journal, 2024)
Abstract Social media is interactive media technologies that facilitate human interaction and socialization. The immediacy of social media makes it easier for all humans to be connected without being limited by distance and reach. With easy reach, social media is also intended in marketing to promote a product or service. Nowadays, many hospitals also take advantage of it. Social media use by patients was found to reduce anxiety about facilities and services and help patients make it easier. In addition, through social media, medical personnel can also improve their image through interaction with patients even before the patient uses the hospital's services. It certainly helps patients to convince themselves and helps media staff to gain patient confidence more quickly. However, many things affect the amount of attention contained in each post. One of them is the time of posting. This study aims to see the effective days for posting on two social media and compare between 2 hospitals. The study uses a descriptive method from the results of manual data collection seen from the accounts concerned. The result is that each account has a different best posting day. The worst day to post on account A does not mean it will also be the worst day to post on account B. In addition, the number of reactions from Facebook is much more than Instagram. It is because Facebook has more users than Instagram. Furthermore, the number of posts is separate from the number of reactions in the form of likes and comments. Because even though the number of posts is few, sometimes it has the most reactions of comments and likes and vice versa.